A gene therapy strategy using a transcription factor decoy of the E2F binding site inhibits smooth muscle proliferation in vivo. - Morishita, R (1995)
The application of DNA technology to regulate the transcription of disease-related genes in vivo has important therapeutic potentials. The transcription factor E2F plays a pivotal role in the coordinated transactivation of cell cycle-regulatory genes such as c-myc, cdc2, and the gene encoding proliferating-cell nuclear antigen (PCNA) that are involved in lesion formation after vascular injury. We hypothesized that double-stranded DNA with high affinity for E2F may be introduced in vivo as a decoy to bind E2F and block the activation of genes mediating cell cycle progression and intimal hyperplasia after vascular injury. Gel mobility-shift assays showed complete competition for E2F binding protein by the E2F decoy. Transfection with E2F decoy inhibited expression of c-myc, cdc2, and the PCNA gene as well as vascular smooth muscle cell proliferation both in vitro and in the in vivo model of rat carotid injury. Furthermore, 2 weeks after in vivo transfection, neointimal formation was significantly prevented by the E2F decoy, and this inhibition continued up to 8 weeks after a single transfection in a dose-dependent manner. Transfer of an E2F decoy can therefore modulate gene expression and inhibit smooth muscle proliferation and vascular lesion formation in vivo.